2020
DOI: 10.3389/fonc.2020.588260
|View full text |Cite
|
Sign up to set email alerts
|

Surgery After Surgery for Vestibular Schwannoma: A Case Series

Abstract: ObjectiveWe retrospectively evaluated the oncological and functional effectiveness of revision surgery for recurrent or remnant vestibular schwannoma (rVS).MethodsWe included 29 consecutive patients with unilateral hearing loss (16 women; mean age: 42.2 years) that underwent surgery for rVS. Previous surgeries included gross total resections (GTRs, n=11) or subtotal resections (n=18); mean times to recurrence were 9.45 and 4.15 years, respectively. House–Brackmann (HB) grading of facial nerve (FN) weakness (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Most vestibular schwannomas have intracanalicular portions. One of the most common causes of vestibular schwannoma recurrence is remnants at the fundus of IAC ( 6 , 7 ). To achieve maximal resection for tumors with intracanalicular extension, care must be taken to prevent concomitant injuries to the posterior SCC, the endolymphatic duct, and a potential HJB ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most vestibular schwannomas have intracanalicular portions. One of the most common causes of vestibular schwannoma recurrence is remnants at the fundus of IAC ( 6 , 7 ). To achieve maximal resection for tumors with intracanalicular extension, care must be taken to prevent concomitant injuries to the posterior SCC, the endolymphatic duct, and a potential HJB ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of acoustic neuromas is highly related to residual tumors in the internal auditory canal (12,13). McKennan et al were the first to use an endoscopic-assisted technique to explore the internal auditory canal, removing the portion of the VS in the internal auditory canal with preservation of facial nerve (17).…”
Section: Discussionmentioning
confidence: 99%
“…At present, an endoscopic-assisted technique for more complex cases of VS has been adopted widely by increasing numbers of neurosurgeons, due to the technological advancement of endoscopic-assisted microsurgery and improved intraoperative neurophysiological monitoring technology ( 10 , 11 ). Endoscopic-assisted microsurgery has greatly reduced postoperative complications, significantly improved the tumor resection rate, and notably has improved the quality of life of patients ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with prior studies by Perry et al and Przepiórka et al that reported no progression after mean follow-up times of 55 and 42 months, respectively. 15,16 Huang et al likewise reported a low progression rate of 6% at a median follow-up time of 74 months, highlighting the efficacy of repeat surgery but the importance of vigilant long-term follow-up in the management of VS. 13 There were several important limitations to this study. This is a retrospective study with a small sample size that is limited by selection bias.…”
Section: Discussionmentioning
confidence: 99%